Explorando el Potencial Educativo del Juego para Estimular la Adopción de Ciencia y Tecnología en la TecnoAcademia Cazucá - Gil Novoa, Héctor Germán
This exciting educational project has designed and developed an interactive game at TecnoAcademia Cazucá to foster interest and passion for science and technology in learners. With the convergence of areas in nanotechnology, graphic design, and software development, the game seeks to encourage the adoption of knowledge in these fundamental areas. Based on projects and with a STEAM focus, the game immerses students in worlds full of challenges and mysteries, where creativity and teamwork are key to solving puzzles that lead to innovation. The results of the game’s implementation are astounding, as there has been a significant increase in confidence, motivation, and improved problem-solving skills. Students show greater interest in exploring the vast world of science and technology, and the game has been a source of inspiration for a new generation of scientists, designers, and developers. The innovative approach of this interactive game has become a powerful teaching tool that transcends traditional educational boundaries. With the combination of STEAM and gamification, the game has proven to be a magic potion that transforms boredom into excitement and apathy into ambition. At TecnoAcademia Cazucá, this project has woven a network of knowledge and creativity, guiding learners towards a future full of borderless possibilities.